Dynamic analysis of a three-fingered deployable metamorphic robotic grasper. (February 2023) - Gao, Changqing; Zhang, Yang; Kang, Xi; Xu, Peng; Li, Bing
Highlights: Propose a distributed dynamic modeling based on multiple motion configurations. Change fingers from complex closed-loop mechanisms to simple equivalent series ones. Present a simplified method for irregular links as rigid-regular-link connections. Combine advantages of Lagrange formalism and Newton-Euler method. Abstract: This paper selects a three-fingered deployable metamorphic robotic grasper as the studied object and presents a distributed dynamic modeling method for the multi-body system based on the metamorphic mechanism. Considering that the grasper contains two independent motion configurations, dynamic models of them are independently established, and then the final dynamic model of the whole grasper is formed. To further improve the modeling accuracy, it is creatively proposed that irregular links can be seen as rigid connections of multiple regular links, by which the dynamic model for the deployment motion of the grasper is firstly established via the Lagrange equation. For the grasping motion, since the finger of the grasper can be equivalent to a planar 4R serial mechanism, the dynamic models of the base mechanism and the basic module are established by the Lagrange equation to obtain the relationships between the driving forces and the equivalent torques. The whole grasper is then established by the recursive Newton-Euler method to enhance the modeling efficiency. Finally, the effectiveness of the dynamic model is well verified by the dynamic simulation.